Dengue Fever: A Public Health Threat to Bangladesh - Sarkar, Santana Rani; Ray, Nitai Chandra (Community Based Medical Journal, 2024)
Dengue fever has become a significant health concern in Bangladesh, with a substantial number of reported cases in recent years. This mosquito-borne viral infection is caused by the dengue virus, transmitted by the Aedes mosquito. The effects of dengue fever can range from mild symptoms such as high fever, muscle and joint pains, to severe complications that can be life-threatening. This paper aims to provide an update on the current situation of dengue fever in Bangladesh, the measures taken by the government and healthcare systems, and the challenges faced in controlling the spread of this disease. In recent years, Bangladesh has experienced a surge in dengue fever cases, particularly during the monsoon season when mosquitoes thrive. According to the Directorate General of Health Services (DGHS), the number of dengue cases has been increasing rapidly, with thousands of reported cases each year. The densely populated urban areas of Dhaka, the capital city, are particularly affected, as inadequate waste management and sanitation contribute to the breeding grounds for mosquitoes. The impact of dengue fever extends beyond health, as it also poses a significant economic burden on affected individuals and the healthcare system. To combat the spread of dengue fever, the government of Bangladesh has taken several measures. These include implementing public awareness campaigns to educate the population about the importance of mosquito control, encouraging practices such as removing standing water and using mosquito repellents, and promoting early diagnosis and treatment. The government has also strengthened its vector control and surveillance programs, focusing on increased mosquito control measures and the early detection of cases. Additionally, efforts have been made to improve healthcare infrastructure and capacity to handle the growing number of dengue cases. However, despite these efforts, challenges remain in controlling the spread of dengue fever in Bangladesh. Factors such as limited resources, inadequate urban planning, and a lack of community participation continue to hinder progress. Furthermore, the emergence of new strains of the dengue virus and the potential for future outbreaks make it crucial to continuously monitor and adapt control strategies. Collaborative efforts between the government, healthcare systems, and the community are essential to effectively manage and prevent the spread of dengue fever in Bangladesh. Only through a comprehensive and sustained approach can the country hope to combat this public health threat effectively. CBMJ 2024 July: vol. 13 no. 02 P: 282-289